Beyond the extremes: Rocks as ultimate refuge for fungi in drylands. (2nd January 2021) - Coleine, Claudia; Stajich, Jason E.; de los Ríos, Asunción; Selbmann, Laura
ABSTRACT: In an era of rapid climate change and expansion of desertification, the extremely harsh conditions of drylands are a true challenge for microbial life. Under drought conditions, where most life forms cannot survive, rocks represent the main refuge for life. Indeed, the endolithic habitat provides thermal buffering, physical stability, and protection against incident ultraviolet (UV) radiation and solar radiation and, to some extent, ensures water retention to microorganisms. The study of these highly specialized extreme-tolerant and extremophiles may provide tools for understanding microbial interactions and processes that allow them to keep their metabolic machinery active under conditions of dryness and oligotrophy that are typically incompatible with active life, up to the dry limits for life. Despite lithobiontic communities being studied all over the world, a comprehensive understanding of their ecology, evolution, and adaptation is still nascent. Herein, we survey the fungal component of these microbial ecosystems. We first provide an overview of the main defined groups (i.e., lichen-forming fungi, black fungi, and yeasts) of the most known and studied Antarctic endolithic communities that are almost the only life forms ensuring ecosystem functionality in the ice-free areas of the continent. For each group, we discuss their main traits and their diversity. Then, we focus on the fungal taxonomy and ecology of other worldwide endolithic communities. Finally, we highlight the utmost importance of a global rock survey in order to have a comprehensive view of the diversity, distribution, and functionality of these fungi in drylands, to obtain tools in desert area management, and as early alarm systems to climate change.